PHOTO SHARING APPLICATION FOR GROUPS USING FLUTTER FRAMEWORK - Calvin Leonardo; Indra Maryati (Jurnal Teknik Informatika (Jutif), 2022)
Taking photos while traveling is certainly familiar today. Sharing the photos taken is also one of the mandatory parts to do, whether traveling alone, as a family, or in a group. Taking and sharing these photos is used for memories and even life satisfaction. In general, the activity of sharing photos that are captured using social media such as WhatsApp, LINE, Instagram, or others. The process of sharing photos on social media has limitations, where the photos that are shared must download first because there is no preview of the photos. This download process will use storage on the user's device. This is certainly not efficient if the photos sent are not in accordance with user context. The development of this photo sharing application uses the SDLC method starting from the analysis process to testing. This application provides a system where users can view photos shared by other users without download. This application will also backup photos on Firebase Storage as well as Google Photos. Image Labeling technology from Google ML Kit also helps to extract the information contained in the image and the extraction results will be used as a hashtag on the photo and can be used to search images using hashtags. The test was carried out on 10 testers and the application can help in sharing photos and there is no need to download to be able to view the shared photos. In addition, the use of image labeling from the Google ML Kit library is also very helpful in performing image searches.